Dissimilarity in radial growth and response to drought of Korshinsk peashrub (Caragana korshinskii Kom.) under different management practices in the western Loess Plateau - Che, Cunwei; Zhang, Mingjun; Yang, Wanmin; Wang, Shengjie; Zhang, Yu; Liu, Lingling (Frontiers in Plant Science, 2024)
Quantitative assessment of tree responses to the local environment can help provide scientific guidance for planted forest management. However, research on the climate-growth relationship of Korshinsk peashrub (Caragana korshinskii Kom.) under different land preparation and post-management (irrigation) conditions is still insufficient. In this study, we collected 223 tree-ring samples from Korshinsk peashrubs using dendroecological methods and systematically quantified the relationships between shrub growth and climatic factors under different management practices in the western Loess Plateau of China. Our findings demonstrated that drought stress caused by scarce precipitation from April to August was the primary factor limiting the growth of Korshinsk peashrubs in the northern and southern mountains of Lanzhou. The “climwin” climate model results showed a weak correlation between natural Korshinsk peashrub growth and drought stress, whereas planted Korshinsk peashrub under rain-fed conditions in the southern mountain was significantly (p<0.05) limited by drought stress from April to August. Moreover, planted Korshinsk peashrub growth under irrigated conditions in the northern mountain was limited only by drought stress in January. Drought model explained 28.9%, 38.3%, and 9.80% of the radial growth variation in Xiguoyuan (XGY), Shuibaozhan (SBZ), and Zhichagou (ZCG) sites, respectively. Artificial supplementary irrigation alleviated the limitation of drought on planted forest growth, which may be implemented for Korshinsk peashrubs planted on sunny slopes, while planted Korshinsk peashrubs under natural rain-fed conditions can be planted on shady slopes through rainwater harvesting and conservation measures such as horizontal ditches and planting holes.